2003
DOI: 10.1128/aac.47.9.2796-2803.2003
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Endotoxin Antagonist E5564 with High-Density Lipoproteins In Vitro: Dependence on Low-Density and Triglyceride-Rich Lipoprotein Concentrations

Abstract: The objective of this study was to determine the distribution profile of the novel endotoxin antagonist E5564 in plasma obtained from fasted human subjects with various lipid concentrations. Radiolabeled E5564 at 1 M was incubated in fasted plasma from seven human subjects with various total cholesterol (TC) and triglyceride (TG) concentrations for 0.5 to 6 h at 37°C. Following these incubations, plasma samples were separated into their lipoprotein and lipoprotein-deficient fractions by ultracentrifugation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…In vitro analyses of the antagonistic activity of E5564 after infusion into healthy volunteers determined that even though E5564 has a long pharmacokinetic half-life and metabolism of E5564 is not observed, E5564 demonstrates a relatively short pharmacodynamic (PD) half-life (Wong et al, 2003). In vivo research further supports this observation by demonstrating that low doses of E5564 are extremely active when coadministered with LPS in the human endotoxemia model but rapidly loses antagonistic activity , likely due to its interaction with plasma lipoproteins (Wasan et al, 2003). Similar loss in PD activity has been observed in a dog endotoxin infusion model (Suganuma et al, 2000).…”
supporting
confidence: 57%
See 2 more Smart Citations
“…In vitro analyses of the antagonistic activity of E5564 after infusion into healthy volunteers determined that even though E5564 has a long pharmacokinetic half-life and metabolism of E5564 is not observed, E5564 demonstrates a relatively short pharmacodynamic (PD) half-life (Wong et al, 2003). In vivo research further supports this observation by demonstrating that low doses of E5564 are extremely active when coadministered with LPS in the human endotoxemia model but rapidly loses antagonistic activity , likely due to its interaction with plasma lipoproteins (Wasan et al, 2003). Similar loss in PD activity has been observed in a dog endotoxin infusion model (Suganuma et al, 2000).…”
supporting
confidence: 57%
“…We have previously shown that loss in antagonistic activity can be observed in vitro in human whole blood (Mullarkey et al, 2003) and is likely due to its interaction with plasma lipoproteins (Rose et al, 2000;Wasan et al, 2003). However, higher concentrations of E5564 (Ն1 M) are not quantitatively inactivated in vitro by whole blood, even after overnight incubation (data not shown), indicating that inactivation of E5564 is either time-dependent or is a "saturable" process.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As expected from in vitro studies (15), eritoran partitions predominantly (ϳ60%) into HDL in plasma. However, as described in Tables 3 and 4, the percentage of eritoran recovered within the TRL fraction proportionally increases with increasing TRL TG or cholesterol.…”
Section: Discussionmentioning
confidence: 73%
“…Preliminary work by Wasan et al using radiolabeled E5531, a similarly structured narrow-spectrum LPS antagonist (16), and, more recently, [ 14 C]eritoran (15) suggests that these types of molecules predominantly bind to high-density lipoproteins (HDL) during incubation in human serum and that interaction with lipoproteins occurs within 5 min, with no measurable redistribution between lipoprotein fractions (16). Studies by Rose and coworkers have supported the importance of plasma lipoprotein binding in influencing the long-term effectiveness of E5531 (8).…”
mentioning
confidence: 99%